Is Intravenous Heparin a Contraindication for TPA in Ischemic Stroke? - Zain Kulairi; Nisha Deol; Renee Tolly; Rohan Manocha; Maliha Naseer (Case Reports in Neurological Medicine)
There are approximately 2 million cardiac catheterizations that occur every year in the United States and with an aging population this number continues to rise. Adverse events due to this procedure occur at low rates and include stroke, arrhythmia, and myocardial infarctions. Due to the high volume of procedures there are a growing number of adverse events. Stroke after cardiac catheterization (SCC) has an incidence between 0.27 and 0.5% and is one of the most debilitating complications leading to high rates of mortality and morbidity. Given the relatively uncommon clinical setting of stroke after cardiac catheterization, treatment protocols regarding the use of IV or IA thrombolysis have not been adequately developed. Herein, we describe a case of a 39-year-old male who developed a stroke following a cardiac catheterization where IV thrombolysis was utilized although the patient was on heparin prior to cardiac catheterization.